(untitled) (Sains Humanika, 2022)
This study was conducted to identify the effect of Solution Focused Brief Therapy (SFBT) group counselling to enhance the self-esteem of primary school students. The objective of this study was to find out the level of self-esteem and the difference in self-esteem score between the control and experimental group before and after the intervention. This study adopted the quasi-experimental research method. The Rosenberg Self Esteem instrument was used in this study to identify the level of self-esteem among primary school students before and after treatment. The study data were analyzed descriptively and inference using paired t-test. The group counselling sessions were observed and SFBT worksheets completed by the respondents were collected and analyzed qualitatively. Findings show that SFBT intervention had a positive effect on raising self-esteem among students in the experimental group from low to medium and high. The results of the study imply a significant difference in the level of self-esteem of students in the experimental group compared to the control group. In conclusion, efforts to identify students with low self-esteem and provide effective interventions such as SFBT at an early stage are very important to cultivate students’self esteem in order to achieve better mental health and wellbeing.